GROWING ROLE OF ROBOTIC-ASSISTED SURGERY IN ADULT PATIENTS - A COMPREHENSIVE REVIEW - Anna Kocik,; Ilona Tadulewicz,; Natalia Nowak,; Mateusz Drozd,; Aleksandra Kozłowska,; Zuzanna Butkowska,; Łucja Komisarczyk,; Tadeusz Kornela,; Aleksandra Góralska,; Zofia Gorzoch-Burduk, (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Robotic-Assisted Surgery (RAS) has transitioned from a technological curiosity to a foundation of modern surgery in the last few years. This review aims to evaluate the current status, clinical outcomes, economic implications, and expanding indications of RAS in adult patients across urologic, gynecologic, colorectal, and general surgical disciplines.Methods: A review of the literature was conducted using PubMed, Scopus, and Web of Science databases for English-language articles published up to 2025. The analysis focused on randomized controlled trials (RCTs), systematic reviews, and large-cohort meta-analyses comparing RAS with open surgery and conventional laparoscopy.Results: The analysis indicates that RAS offers superior visualization and improved ergonomics compared to conventional laparoscopy. In urology, RAS has become the gold standard for prostatectomy, showing statistically significant reductions in estimated blood loss (EBL) and improved functional recovery (continence and potency). In gynecology and general surgery, RAS demonstrates lower conversion rates to open surgery, particularly in obese cohorts and deep pelvic dissections. While operative times are frequently longer during the learning curve, total length of hospital stay is consistently reduced.Conclusions: Robotic surgery has proven advantageous in minimizing patient trauma and assisting with complex cases where conventional laparoscopy struggles. The primary barrier remains the high upfront cost; however, these expenses may be offset over time by reduced length of stay and lower complication rates, strengthening the economic case for RAS.